The effects of a health literacy-promoting program based on the family-centered empowerment model on delayed dyspnea and fatigue in patients with COVID-19: A randomized clinical trial - Nasim Abbaszadeh; Zohreh Vafadar; Hosein Mahmoudi; Robabe Khalili (Kashan University of Medical Sciences, 2024)
Background: Delayed dyspnea and fatigue are prevalent symptoms among patients with COVID-19, and family caregivers play a crucial role in their care.Objectives: This study aimed to investigate the effects of a health literacy-promoting intervention based on the Family-Centered Empowerment Model (FCEM) on delayed dyspnea and fatigue in patients with COVID-19.Methods: A randomized controlled trial was conducted at Chamran Hospital in Tehran, Iran, in 2022, involving 70 pairs of COVID-19 patients and their primary family caregivers. Patients were randomly assigned to either the intervention group or the control group using a block randomization method. The intervention group received two 30-minute training sessions for primary family caregivers, while the control group received routine training. Data were collected using the Health Literacy Instrument for Adults, the Fatigue Severity Scale, and the Borg Dyspnea Scale before, one week after, and six weeks after the intervention. The chi-square and Fisher's exact tests, Mann-Whitney test, Friedman test, repeated measures analysis of variance, and Pearson correlation test were used to analyze the data.Results: The mean baseline health literacy score was higher in the control group; however, the increase in health literacy was significantly greater in the intervention group (F=75.31; Df=1.73; P<0.000; Effect size=0.52). The intervention group also experienced a greater reduction in dyspnea during the study (F=13.90; Df=2; P<0.000; Effect size=0.17) and a greater reduction in fatigue (F=10.65; Df=1.18; P<0.001; Effect size=0.13) despite having a higher baseline fatigue score.Conclusion: The health literacy-promoting intervention based on FCEM significantly improved family caregivers' health literacy and reduced delayed fatigue and dyspnea in patients with COVID-19. Nurses are encouraged to implement similar programs to mitigate delayed complications in patients with COVID-19.